Development of smart films based on soy protein and cow horn dissolved in a deep eutectic solvent: Physicochemical and environmental assessment - Uribarrena, Maialen (2025)
With the urge to reduce the use of petroleum-based materials, the aim of this work is to valorize biowaste to develop smart films through a sustainable fabrication way. In this regard, choline chloride/urea (1:2) deep eutectic solvent (DES) at different concentrations (25, 40, 50 and 75 wt%) was used to dissolve cow horn, used as reinforcement agent in soy protein films. The film fabrication was carried out by compression molding, a fast and cost-effective. As proved by SEM/EDX, cow horn was well-dispersed in the films, suggesting a homogeneous distribution of the sulfur from the cysteine present in keratin, the main component of cow horn. FTIR spectroscopy suggested interactions between the components of the formulation, which reduce the water uptake from 180 % to 140 %. Additionally, the films could be heat-sealed. With the aim of developing smart films, blueberry extract was incorporated into the formulation. This extract provided the films with pH sensitivity, which was followed by the film color change in presence of ammonia vapor. In particular, it is worth noting the ability of those films prepared with 40 wt% Horn/DES and 15 wt% blueberry extract to detect food spoilage. Finally, the environmental assessment of the films showed a minimal environmental impact of the procedure, with DES preparation and soybean production as the main relative contributors of the environmental load.